Assessing phylogenetic relationships of Lycium samples using RAPD and entropy theory - Yin Xiao-lin; Fang Kai-tai; Liang Yi-zeng; Wong Ricky NS; Wyha Amber (Acta Pharmacologica Sinica, 2016)
Aim: To evaluate the phylogenetic relationships among related species of Lycium samples. Methods: Random amplified polymorphic DNA (RAPD) fingerprinting and lab-on-a-chip electrophoresis techniques were used to analyze the characteristics of Lycium species. Seven species and 3 varieties of Lycium were studied. Based on RAPD fingerprint data obtained from 11 primers, we proposed a new index, called dispersivity, using entropy theory and projection methods to depict the diversity of the DNA fingerprints. Results: Using the proposed dispersivity, primers were sorted and the dendrograms of the 7 species and 3 varieties of Lycium were constructed synthetically by merging primer information. Conclusion: Phylogenetic relationships among Lycium samples were constructed synthetically based on RAPD fingerprint data generated from 11 primers.